2005
DOI: 10.1007/s00415-005-0699-x
|View full text |Cite
|
Sign up to set email alerts
|

Phobic postural vertigo

Abstract: One hundred and six patients diagnosed between 1987 and 1998 to have somatoform phobic postural vertigo were examined in a follow-up study with a self-evaluating questionnaire. The improvement rate after a mean follow-up time of 8.5 years (5 to 15.9 years) was 75% (27% of the patients reported a complete remission). While the majority of these patients experienced improvement or remission during the first year after assessment of diagnosis and a short-term psychotherapeutic approach, some patients also had con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(14 citation statements)
references
References 26 publications
0
9
0
5
Order By: Relevance
“…26,27 Anxiety has been demonstrated to play an additional role in dizziness, which may be considered in some cases a somatoform disorder arising from stressful events. 28,29 Some Authors focused on the high rate to get both dizziness and anxiety in the elderly 26,30 Dizziness in the elderly has adverse psychological and social effects due to the decrease of performances in daily living activities and the increase of fear or risk of falling. 31 A recent study confirmed a significant association with older age and anxiety, in particular with higher DHI questionnaire score in emotional domain, which appears to be the most important predictor factor for the occurrence of RD.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 Anxiety has been demonstrated to play an additional role in dizziness, which may be considered in some cases a somatoform disorder arising from stressful events. 28,29 Some Authors focused on the high rate to get both dizziness and anxiety in the elderly 26,30 Dizziness in the elderly has adverse psychological and social effects due to the decrease of performances in daily living activities and the increase of fear or risk of falling. 31 A recent study confirmed a significant association with older age and anxiety, in particular with higher DHI questionnaire score in emotional domain, which appears to be the most important predictor factor for the occurrence of RD.…”
Section: Resultsmentioning
confidence: 99%
“…Although all three disorders might resemble each other very much, they are seen as different entities. VVM, PPV and CSD are often mistaken since all are associated (either primary or secondary) with psychiatric disorders such as anxiety, depression, panic attacks and even obsessive-compulsive personality traits [ 44 , 51 , 52 ]. PPV is characterized by a persistent sense of unsteadiness or postural imbalance and recurrent dizziness attacks [ 48 , 49 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that patient education can be a key first step in the therapeutic process. 9,22 Physicians who suspect CSD or a psychogenic origin should discuss psychosocial issues with these patients and the ways in which psychiatric disorders and stress can cause or exacerbate chronic dizziness. For instance, a physician can initiate this conversation by focusing on the topic of stress: "In many patients, stress can also contribute to or worsen dizziness.…”
Section: Surf E22mentioning
confidence: 99%